Primary schwannoma of the appendix: A rare case report with brief review of literature (Indian Journal of Case Reports, 2026)
Appendiceal schwannoma is an exceptionally rare benign mesenchymal tumor and frequently poses a diagnostic challenge due to non-specific clinical and radiological findings. We report a case of appendiceal schwannoma in a 40-year-old female who presented with right iliac fossa pain and was clinically and radiologically suspected to have appendiceal carcinoma. Laparoscopic radical appendicectomy was performed. Histopathological examination revealed a spindle cell neoplasm with nuclear palisading, and immunohistochemistry showed diffuse strong SOX10 positivity with negativity for CD117 and H-caldesmon, confirming the diagnosis. The patient remains asymptomatic on follow-up. A brief review of reported cases is provided.